Increased brain size of the dwarf Channel Island fox (Urocyon littoralis) challenges “Island Syndrome” and suggests little evidence of domestication - Kimberly A. Schoenberger; Xiaoming Wang; Suzanne Edmands (PLoS ONE, 2025)
Although changes in overall body size during species’ island adaptation is a well-established phenomenon, there are mixed findings regarding how brain size changes within resource-limited insular environments. Work on this issue has focused on fossil species and herbivores, with limited studies on carnivores and extant island species. Here, we aim to close this knowledge gap and expand our understanding of brain size evolution by examining the relative brain size of the extant island canid, the Channel Island fox (Urocyon littoralis) amongst its six island-specific subspecies and in comparison to its larger mainland relative, the gray fox (Urocyon cinereoargenteus). As the island fox was likely brought to the southern Channel Islands by indigenous peoples, this research is also relevant in exploring the impact of human transport and potential domestication on brain size. Our endocranial analysis found that foxes across five of the islands have a moderately higher relative brain size in comparison to the gray fox, with only the second smallest, most geographically isolated island, San Nicolas, exhibiting reduction. No significant differences in encephalization were found between sexes within any subspecies. These findings suggest that the selective pressures driving reduced body size on islands may not outweigh the adaptive benefits of increased brain size, with the exception of highly resource-constrained environments such as on San Nicolas. Disparity in brain size among the three southern islands and the increased encephalization of San Clemente and Santa Catalina foxes compared to the mainland gray fox further suggests that although humans may have facilitated transport of the southern island foxes, true domestication was likely not practiced. Broadly, this research indicates that brain size reduction is not a straightforward trait of island adaptation, and changes in insular species’ brain size will vary in conjunction with island-specific selective pressures.